2020
DOI: 10.1186/s13045-020-00920-3
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1 (HMGB1): a pivotal regulator of hematopoietic malignancies

Abstract: High mobility group box 1 (HMGB1) is a nonhistone chromatin-associated protein that has been widely reported to play a pivotal role in the pathogenesis of hematopoietic malignancies. As a representative damage-associated molecular pattern (DAMP), HMGB1 normally exists inside cells but can be secreted into the extracellular environment through passive or active release. Extracellular HMGB1 binds with several different receptors and interactors to mediate the proliferation, differentiation, mobilization, and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 194 publications
2
94
0
Order By: Relevance
“…At the membrane, HMGB1 promotes axonal sprouting and neurite growth. HMGB1 can be transferred to extracellular context by two ways: active secretion from immunocompetent cells or passive release from apoptotic or necrotic cells, participating in immune responses autophagy and inhibits apoptosis of tumor cells to induce chemotherapy resistance [15]. On the other hand, HMGB1 plays a protective role in the suppression of tumor and tumor chemoradiotherapy and immunotherapy.…”
Section: The Dual Effects Of Hmgb1 In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…At the membrane, HMGB1 promotes axonal sprouting and neurite growth. HMGB1 can be transferred to extracellular context by two ways: active secretion from immunocompetent cells or passive release from apoptotic or necrotic cells, participating in immune responses autophagy and inhibits apoptosis of tumor cells to induce chemotherapy resistance [15]. On the other hand, HMGB1 plays a protective role in the suppression of tumor and tumor chemoradiotherapy and immunotherapy.…”
Section: The Dual Effects Of Hmgb1 In Cancermentioning
confidence: 99%
“…But it remains to be studied whether HMGB1 interacts with other tumor suppressors or oncoproteins. Extracellular HMGB1 enhances chemotherapy efficacy by transforming tumor cells from apoptosis to senescence [15]. In addition, HMGB1 can mediate immunogenic cell death during chemoradiotherapy and enhance anti-tumor immunity.…”
Section: The Dual Effects Of Hmgb1 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1 is a highly conserved nuclear protein that has been proven to be upregulated in various kinds of cancers. Studies demonstrated that HMGB1 was over-expressed in three leukemia cell lines K562,HL60 and Jurkat) and was correlated to the stage of leukemia [20,21] . And it is reported that the expression of HMGB1 in primary and relapsed leukemia was much higher than healthy people and patients with complete remission [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, besides the proposed role in lymphocyte membrane invagination [75,76], DG associated with GEVs may evoke responses in human skin cells by activating PKC signaling, thereby mediating inter-cellular communication between plant and human cells. Given that PKC can in turn regulate HMGB1 activity via phosphorylation [77], the increased intracellular expression of HMGB1 in GEV-treated melanocytes may be partially attributable to vesicular DG-activated PKC signaling. Thus, it may be worth investigating whether GEVs can activate PKC signaling and whether inhibition of that signaling can eliminate GEV-induced anti-senescence phenotypes in human melanocytes.…”
Section: Discussionmentioning
confidence: 99%